Study on the effects of tio2 doping on pure sno2 for ethanol gas sensing properties - Pavinthran, Maran+ (Universiti Sains Malaysia, 2017)
The aim of this research is to study on the effects of different TiO2 weight % doping on SnO2 ethanol gas sensing properties. Three different TiO2 weight % doping of 20, 40 and 60 wt% on pure SnO2 are synthesized via precipitation method, while pure SnO2 powder is synthesized via sol-gel method. The active layer is then deposited on 10mm x 10mm aluminate substrate via screen printing method. The samples have been characterized by X-Ray Powder Diffraction (XRD). All the samples are tested with different temperatures ranging from 150oC to 450oC at ethanol concentration of 1000ppm. The optimum temperature for each samples are obtained by determining temperature the sensors exhibit highest gas sensing performance in terms of sensitivity and response-recovery time. The sensors are then tested in variation of ethanol gas concentration ranging from 150ppm to 1000ppm at respective optimum temperature. Pure SnO2 sample showed maximum response of 29.76 at 350oC, which is the highest among all the samples. In addition, the response time is 7s, the lowest among all the samples and records the highest recovery time of 99s among all samples due to lowest baseline resistance achieved. When tested with variation of ethanol gas concentration, pure SnO2 exhibits maximum response of 49.03 at 1000 ppm. Pure SnO2 active material remains the ideal sensor for temperature range of 250oC to 350oC and 150ppm to 1000ppm for ethanol temperature range compared to hetero structure (TiO2 doped SnO2) sensor